The Use and Efficacy of Biological Therapies for Inflammatory Bowel Disease in a Danish Tertiary Centre 2010–2020. Issue 4 (3rd November 2022) - Wewer, Mads Damsgaard; Arp, Laura; Sarikaya, Melek; Felding, Oluf Krautwald; Vind, Ida; Pedersen, Gitte; Mertz-Nielsen, Anette; Kiszka-Kanowitz, Marianne; Boysen, Trine; Theede, Klaus; Petersen, Andreas Munk; Nordgaard-Lassen, Inge; et al.
Abstract: Background: Patients with inflammatory bowel disease (IBD) who receive biologicals frequently experience lack or loss of response. Our aim was to describe the use and efficacy of biological therapy in a tertiary IBD center. Methods: We included all bio-naive IBD patients who initiated biological therapy between 2010 and 2020 at our centre. Their medical records were reviewed. Results: The population consisted of 327 Crohn's disease (CD) patients, 291 ulcerative colitis (UC) patients, and 3 patients with IBD unclassified (IBDU). The median follow-up was 3 years (interquartile range = 2–5) after initiating therapy. The annual number of patients initiating biological therapy rose from 29 (2010) to 85 (2019). Most patients (457, 73.6%) received 1 biological drug; 164 (26.4%) patients received 2 or more biologicals. Primary lack of response was observed in 36.4% (106/291) and 17.4% (57/327) of UC and CD patients; loss of response was observed in 27.1% (79/291) and 31.5% (103/327) of UC and CD patients, respectively. The 5-year surgery rates were 26.6% and 20.4% in UC and CD patients, respectively. Multivariate Cox regression showed that treatment with thiopurine reduced the likelihood of needing to switch biological therapy, requiring surgery or corticosteroids in UC patients (HR: 0.745, 95% CI: 0.559–0.993), but not in CD patients (HR: 0.996, 95% CI: 0.736–1.349). Conclusions: The annual number of IBD patients initiated on biological therapy increased considerably between 2010 and 2020. One-quarter of these patients required surgery after 5 years. Our findings suggest a beneficial effect of concurrent thiopurines for UC patients receiving biologicals, but this was not found for CD patients. This effect in UC patients was not observed when we included patients initiating thiopurines up to 6 months after the introduction of biological therapy. Lay Summary: We included all inflammatory bowel disease (IBD) patients, who started biological therapy between 2010 and 2020 at our department in Denmark. One-quarter of these patients required surgery after five years. Concurrent medication with thiopurines seemed to be beneficial in some patients.